Longman dictionary of contemporary english - pearson longman (London Pearson longman, 2010)
230,000 words, Phrases, and meanings also contain 3000 most frequnt words in spoken and writen english highlighted and integrated Thesaurus with over 18.00 synonyms, antonyms, and related words
"new edtion for advanced learners"
12
Keywords: English language -- Terms and phrases; English language -- dictinaries